EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) DENGAN ASSESMENT FOR LEARNING (AfL) PADA MATERI HIMPUNAN DITINJAU DARI KECERDASAN INTRAPERSONAL SISWA SEKOLAH MENENGAH PERTAMA SE-KABUPATEN TULUNGAGUNG - Addin Zuhrotul ‘Aini; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Universitas Sebelas Maret, 2016)
Abstract: The aims of this study were to investigate: (1) among the model of NHT, NHT with AfL and classical model, which learning model can give better mathematics learning achievement. (2) which student’s have better mathematics learning achievement, those with high, medium, or low intrapersonal intelligence. (3) viewed from learning models, which student’s have better mathematics learning achievement those with high, medium or low intrapersonal intelligence. (4) viewed from intrapersonal intelligence, which learning model produces better mathematics learning achievement NHT with AfL, NHT or classical learning model. This research used quasi experimental method with its population included all of students of state junior high school in Tulungagung Regency. Sampling was done by stratified cluster random sampling technique. The size of the samples was 266 students. The data collection technique was include the documentation method to get 2013/2014 initial capability data before the experiment, achievement test for mathematics student’s achievements data, and questioner of intrapersonal intelligence. The data was analyzed using analysis of variance. Based on the analysis, it can be concluded as follows. (1) The model of NHT with AfL providing better mathematics learning achievement than the model of NHT and classical, while the model of NHT providing better mathematics learning achievement than classical model. (2) Students with high intrapersonal intelligence have better mathematics learning achievement than students with medium or low intrapersonal intelligence, students with medium intrapersonal intelligence have better mathematics achievement than student’s with low intrapersonal intelligence. (3) Viewed from learning models, student’s with high intrapersonal intelligence have better mathematics learning achievement than medium or low, and medium intrapersonal intelligence have better mathematics learning than low intrapersonal intelligence. (4) Viewed from intrapersonal intelligence, mathematics learning using NHT with AfL resulted students with better mathematics learning achievement than using NHT and classical learning model, learning mathematics using NHT resulted students with better mathematics learning achievement than using classical learning model.Keywords: Numbered Head Together, Assessment for Learning, Intrapersonal Intelligence